Comparison of Diagnostic Accuracy of Conventional Intraoral Periapical and Direct Digital Radiographs in Detecting Interdental Bone Loss - Ashwinirani S.R.; Girish Suragimath; Jaishankar H.P.; Prasad Kulkarni; Shobha C. Bijjaragi; Varsha Ajit Sangle (Journal of Clinical and Diagnostic Research, 2015)
Background: Periodontitis is an inflammatory disease of the supporting tissues of the teeth caused by specific microorganisms, resulting in destruction of the periodontal ligament and alveolar bone. Progressive loss of alveolar bone is the salient feature of periodontal disease. Accurate detection of periodontal disease with the use of radiographs helps in diagnosis, treatment and prognosis. Aims: The present study aims to compare the efficacy of conventional intraoral periapical (IOPA) and direct digital radiographs (RVG) in detecting interdental alveolar bone loss using intrasurgical (IS) measurements as the gold standard. Materials and Methods: Thirty patients elected to undergo periodontal flap surgery with periodontitis computing to 60 interdental alveolar defects on mandibular first molars were considered. IOPA and RVG were captured using standardized techniques. Bone loss measurements in IOPA and RVG were compared to the IS measurements. Statistical Analysis: Statistical analysis was carried out using student t test and ANOVA with the help of SPSS software and p-value <0.05 was considered as significant. Results: Both IOPA and RVG underestimated the bone loss measurements when compared to IS measurements which was statistically significant (p<0.0001). Bone loss measurements in RVG were closer to IS measurements than IOPA. Conclusion: Both the radiographic techniques IOPA and RVG underestimated bone loss by 1.5–2.5 mm. RVG was superior to IOPA for the detection of interdental bone loss due to reduced time and radiation exposure to obtain the same diagnostic information.